2005
DOI: 10.1364/ao.44.004775
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous stratospheric gas and aerosol retrievals from broadband infrared occultation measurements

Abstract: The inversion method for simultaneous gas (O3, NO2, HNO3, N2O, CH4, H2O, CFC-11, CFC-12, N2O5, and ClONO2) and aerosol retrievals from broadband continuous IR spectra of occultation measurements is described. Both gas and aerosol physical modeling with consideration of the multicomponent character of aerosol and polar stratospheric clouds (PSCs) are used to minimize the difference between measured and modeled transmittance spectra under smoothness constraints imposed on particle-size distributions for each PSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The Improved Limb Atmospheric Spectrometers ILAS and ILAS-II used the solar occultation technique which measures the absorption of stratospheric species in the infrared region of solar radiation Oshchepkov et al, 2005 (Nakajima et al, 2006b).…”
Section: Ilas/ilas-iimentioning
confidence: 99%
“…The Improved Limb Atmospheric Spectrometers ILAS and ILAS-II used the solar occultation technique which measures the absorption of stratospheric species in the infrared region of solar radiation Oshchepkov et al, 2005 (Nakajima et al, 2006b).…”
Section: Ilas/ilas-iimentioning
confidence: 99%
“…The inversion procedure yielding simultaneous gas and aerosol retrievals from occultation measurements using aerosol physical modeling has been described elsewhere [ Oshchepkov et al , 2005]. The main features of the retrieval scheme and the assumptions in routine ILAS data processing are given below.…”
Section: Methodsmentioning
confidence: 99%
“…However, real AEC spectra could not always be represented as broken straight lines derived from linear interpolation. This problem was more likely with high aerosol amounts, such as those common in PSC observations [ Yokota et al , 2002; Oshchepkov et al , 2002, 2005]. Simultaneous retrievals of gas mixing ratios and aerosol spectra [ Oshchepkov et al , 2002] was shown to alleviate this problem and allow the extraction of useful aerosol information in all ILAS channels.…”
Section: Introductionmentioning
confidence: 99%
“…The locations of the maxima of the retrieved particle size distribution are shown to be in a good agreement with those for the original size distributions. The fact that the half width of the retrieved particle size distribution is subject to overestimation, as well as the magnitude of the particle size distribution at the position of its maximum experiencing underestimation as the particle sizes decrease, is explained by the limited sensitivity of the infrared data with respect to size composition of small particles [ Oshchepkov et al , 2005]. Indeed, the highest biases hold for very small binary H 2 SO 4 /H 2 O droplets.…”
Section: Retrievalsmentioning
confidence: 99%
“…In addition, the processing of each LTS spectrum demands consideration of different chemical compositions, even for reliable retrievals of the particle size distribution. It is therefore not probable that such an approach is optimal for the processing of spaceborne occultation measurements when, along with LTS, we need to allow for other PSC and gas components simultaneously [ Oshchepkov et al , 2005].…”
Section: Bicomponent Approximationmentioning
confidence: 99%